Stress-Induced Anxiety- and Depressive-Like Phenotype Associated with Transient Reduction in Neurogenesis in Adult Nestin- CreERT2/Diphtheria Toxin Fragment A Transgenic Mice - Yun, Sanghee; Donovan, Michael H.; Ross, Michele N.; Richardson, Devon R.; Reister, Robin; Farnbauch, Laure A.; Fischer, Stephanie J.; Riethmacher, Dieter; Gershenfeld, Howard K.; Lagace, Diane C.; Eisch, Amelia J. (PLOS ONE, 2016)
Depression and anxiety involve hippocampal dysfunction, but the specific relationship between these mood disorders and adult hippocampal dentate gyrus neurogenesis remains unclear. In both humans with MDD and rodent models of depression, administration of antidepressants increases DG progenitor and granule cell number, yet rodents with induced ablation of DG neurogenesis typically do not demonstrate depressive- or anxiety-like behaviors. The conflicting data may be explained by the varied duration and degree to which adult neurogenesis is reduced in different rodent neurogenesis ablation models. In order to test this hypothesis we examined how a transient–rather than permanent–inducible reduction in neurogenesis would alter depressive- and anxiety-like behaviors. Transgenic Nestin-CreERT2/floxed diphtheria toxin fragment A (DTA) mice (Cre+DTA+) and littermates (Cre+DTA-; control) were given tamoxifen (TAM) to induce recombination and decrease nestin-expressing stem cells and their progeny. The decreased neurogenesis was transient: 12 days post-TAM Cre+DTA+ mice had fewer DG proliferating Ki67+ cells and fewer DCX+ neuroblasts/immature neurons relative to control, but 30 days post-TAM Cre+DTA+mice had the same DCX+ cell number as control. This ability of DG neurogenesis to recover after partial ablation also correlated with changes in behavior. Relative to control, Cre+DTA+ mice tested between 12–30 days post-TAM displayed indices of a stress-induced anxiety phenotype–longer latency to consume highly palatable food in the unfamiliar cage in the novelty-induced hypophagia test, and a depression phenotype–longer time of immobility in the tail suspension test, but Cre+DTA+ mice tested after 30 days post-TAM did not. These findings suggest a functional association between adult neurogenesis and stress induced anxiety- and depressive-like behaviors, where induced reduction in DCX+ cells at the time of behavioral testing is coupled with stress-induced anxiety and a depressive phenotype, and recovery of DCX+ cell number corresponds to normalization of these behaviors.
Keywords: hippocampal dysfunction; hippocampal dentate gyrus neurogenesis; neurogenesis; floxed diphtheria toxin fragment